Trends in prevalence and treatment of antepartum and postpartum depression in the United States: Data from the national health and nutrition examination survey (NHANES) 2007 to 2018 - Rebecca M. Gardner; Pervez Sultan; Rebecca A. Bernert; Julia F. Simard (PLoS ONE, 2025)
Objectives (1) To assess the prevalence of depression and treatment rates in antepartum and postpartum women compared to a control group of reproductive-age women over a 12-year period, and (2) To determine demographic characteristics associated with depression. Methods National Health and Nutrition Examination Survey data (2007–2018) were used. 5412 controls, 314 antepartum women, and 455 postpartum women were analyzed. Outcomes included depression prevalence, defined as moderate to severe depressive symptoms measured by Patient Health Questionnaire-9 (PHQ-9) scores ≥10 or self-reported antidepressant use; and treatment, defined as antidepressant prescription and/or mental health care services in the past 12 months. Multivariable logistic regression adjusted for age, insurance, race/ethnicity, education, and marital status estimated odds ratios and 95% confidence intervals. Results Depression prevalence was 20.2% in controls (95% CI 18.5–21.9), 9.7% in antepartum (6.3–14.1), and 12.8% in postpartum women (9.3–17.1). Mental health care service utilization increased for postpartum women in 2017–2018 (22.0%, 10.6–37.7). In those with depression, control and postpartum groups had similar treatment rates (70%, p = 0.894) compared to antepartum women (51%, p = 0.051). Antidepressant use was the most common treatment reported in all groups. Those who were married or had private insurance had the lowest depression rates in their respective categories. After adjusting for confounders, antepartum and postpartum women had lower odds of depression compared to controls. When the outcome was PHQ-9 ≥ 10 alone, these associations persisted. Conclusion In a nationally representative sample, depression prevalence was lower in perinatal women compared to reproductive-age controls, and treatment rates were lowest in antepartum women with prevalent depression. Mental health care services may have increased for postpartum women due to the US Preventive Services Task Force 2016 recommendations, which endorsed psychotherapy for postpartum women. Even so, antidepressants were the most reported treatment among perinatal women, despite psychotherapy being the first-line recommended treatment for this population.